Varieties In The Use Of English Speech Acts On Radio EBS And Istara FM Surabaya - Dwi Anggara Asianti (1994)
Speaking a language is performing a speech acts 1979: 16). The kind OT speech related to the speech illocutionary acts. It is an action in saying (Austin in Pateda, 1997: 13). Generally a speaker performs actions withins communication with othe people. Communication occurs between two people or between one and public. The public communication occurs by using the radio, as one of the media. Radio is one OT the tools of the communication which sends messages to the listeners by using various illocutionary acts. The variety of illocutionary acts in some radio stations are in English. The aim of this research is to find out their varieties and frequency and if there are some differences in radio.